Mechanoresponsive lipid-protein nanoglobules facilitate reversible fibre formation in velvet worm slime - Alexander Baer (Nature Portfolio, 2017)
Velvet worms expel a fluid slime that, under shear force, forms stiff fibres that can be dissolved and then regenerated. Here, the authors reveal that the recyclability of these biopolymers relies on mechanoresponsive lipid-protein nanoglobules in the slime that reversibly self-assemble into fibrils.